Liver steatosis and fibrosis in people with human immunodeficiency virus in West Africa and the relationship with hepatitis B virus coinfection. Issue 11 (14th September 2022) - Villa, Giovanni; Owusu, Dorcas; Smith, Colette; Azumah, Marilyn; Abdullahi, Adam; Phillips, Suzannah; Sayeed, Laila; Austin, Harrison; Chadwick, David; Phillips, Richard Odame; Geretti, Anna Maria
Abstract: There is a heavy burden of liver disease in West Africa. While the role of hepatitis B virus (HBV) infection is well recognized, less is known about the contributing role of liver steatosis and how the two interact in the context of human immunodeficiency virus (HIV) infection. Adults with HIV in Ghana underwent FibroScan measurements to determine prevalence of liver steatosis (expressed as controlled attenuation parameter [CAP]) and fibrosis (expressed as liver stiffness [LS]). We explored contributing factors in linear regression models, including demographics, lifestyle characteristics, medical history, HIV and HBV status, and measurements of metabolic syndrome. Among 329 adults (72.3% women; median age, 47 years), 322 (97.9%) were on antiretroviral therapy (median duration, 8.9 years). CD4 counts were preserved (median, 619 cells/mm 3 ); plasma HIV RNA was fully suppressed in 162 (50.3%) of the treated participants. Cigarette smoking, excessive alcohol consumption, and use of traditional or herbal remedies were uncommon (6.1%, 1.8%, 3.3%, respectively). Largely undiagnosed metabolic syndrome was detected in 87 (26.4%) participants. We obtained readings indicative of ≥S2 steatosis and ≥F2 fibrosis in 43 (13.1%) and 55 (16.7%) participants, respectively. Higher CAP values were associated with metabolic syndrome and longer prior stavudine exposure. Higher LS values were associated with male sex, higher HIV RNA, and higher CAP values. Relative to people without HBV, those with HBV ( n = 90) had a similar prevalence of ≥S2 steatosis but a higher prevalence of ≥F2 fibrosis (36.7% vs. 9.2%, p < 0.0001) and concomitant ≥S2 steatosis and ≥F2 fibrosis (9.1% vs. 1.3%, p < 0.001). Conclusion : Both HBV and liver steatosis pose a threat to long‐term liver health among people with HIV in West Africa. Urgently required interventions include improving HIV suppression and diagnosing and managing determinants of the metabolic syndrome. Abstract : We determined the prevalence of both liver steatosis and liver fibrosis in a HIV cohort in Ghana using a portable FibroScan, and we interpreted the data within a broad context, including measurements that are not part of routine HIV care in Kumasi. We identified two main reasons for concern: (1) metabolic syndrome was common and a predictor of liver steatosis, but it was largely undiagnosed and untreated; (2) only about half of the population had a suppressed HIV RNA load while receiving antiretroviral therapy, and uncontrolled virus replication was a predictor of liver fibrosis regardless of HBV status.image